1970
DOI: 10.1002/j.1537-2197.1970.tb09830.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy Applied to Cucurbita Relationships

Abstract: In a numerical study of taxonomic relationships in Cucurbita, the inclusion of F1 interspecific hybrids did not materially alter the species grouping in the phenogram. The F1 interspecific hybrids tend to cluster with one of the parent species or species groups unless the parents are widely divergent. Also, the F1 interspecific hybrids between wild and domesticated species cluster with the wild parent Both parent species or species groups of an F1 interspecific hybrid can usually be determined from Q‐correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…However, raw distance values were even better than UPGMA. Similar results were reported by Bemis et al (1970) and Barrett and Rhodes (1976). If recognition of hybrids is the goal, one should simply calculate a distance matrix and use it to locate taxa closest to the putative hybrid or, vice versa, taxa closest to putative parents.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, raw distance values were even better than UPGMA. Similar results were reported by Bemis et al (1970) and Barrett and Rhodes (1976). If recognition of hybrids is the goal, one should simply calculate a distance matrix and use it to locate taxa closest to the putative hybrid or, vice versa, taxa closest to putative parents.…”
Section: Discussionsupporting
confidence: 74%
“…In terms of placement of hybrids by clustering methods, the results presented here largely concur with previous work although, to my knowledge, hybrids have not been previously investigated using NJ. Hybrids of known parental origin are usually placed with one or both parents (e.g., Heiser et al 1965;Bemis et al 1970;Rhodes et al 1970; Barrett and Rhodes 1976;Schilling and Heiser 1976;Edmonds 1978), and hybrids that share one parent often cluster together (e.g., Heiser et al 1965;Barrett and Rhodes 1976). Hybrids between distantly related parents may be placed far from either parent (e.g., Schilling and Heiser 1976), sometimes affecting other taxa in an analysis (e.g., Rhodes et al 1970).…”
Section: Discussionmentioning
confidence: 99%
“…In an initial survey with three enzyme staining systems, Puchalski and Robinson (1978) reported general agreement with an earlier taxonomic treatment of relationships among Cucurbita species (Bemis et al 1970). More extensive surveys of isozyme variation among Cucurbita species (Puchalski and Robinson 1990) and, more specifically, in wild, weedy, domesticated Mexican Cucurbita presented more complex views of genetic differentiation and gene flow among taxa (Wilson 1989).…”
Section: Germplasm Characterizationsupporting
confidence: 58%
“…Moreover, Bemis et al (1970) found that F I interspecific hybrids in the genus Cucurb ita tended to cluster with one of the parental species, instead of being intermediate, and also that the hybrids between wild and domestic species clustered with the wild parent. More recently, Pembleton and Baker (1978) found that hybrids between two chromosomal races of a pocket gopher, Geomys bursarius, resembled the larger parental form in a discriminant analysis based on seven metric characters, a result similar to mine with tesselatus, which also resembles the larger parental species, septemvittatus, in size.…”
Section: Morphological Interactions Betweenmentioning
confidence: 96%